Kitchen Komposter (c) - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
Kitchen Komposter (c) Careful investigation has shown that when garbage is divided into different categories such as plastic, paper, metals, etc., food waste accounts for about 8% of the refuse. This food waste is all decomposable and rather than...